การปรับปรุงประสิทธิภาพการดำเนินงานคลังพัสดุ : กรณีศึกษา หน่วยงานรัฐวิสาหกิจ - รัฐวุฒิ วงษ์วิทย์ (จุฬาลงกรณ์มหาวิทยาลัย, 2007)
The thesis study of warehousing operations of the state enterprise. The objective of thesis is improvement efficiency of warehousing operations. Problem found due to study ware 1.The warehouse is not have systematic method of storage and arrangement 2. Receiving and storage ,order picking and checking takes longtime and has errors. Which procedure of improvement initial using 5s, grouping inventories by multi criteria, specification quantity maximum and minimum of storage, Design storage layout , location assignment and coding and development programming for increase efficiency warehousing operations. The research results are the storage location in order to arrange the goods in orderly is more convenient for order picking, time reduction in procedure of storage and order picking, the information is more accuracy. These improvement can be the guideline for the other warehouse. The result of improving efficiency of warehousing operations are 1. Accuracy of order picking document 1.40 % increasing. 2. Accuracy of picking 1.31 % increasing. 3. Average time of receive and storage 4.03 % reducing. 4. Average time of order picking 37.95 % reducing. 5. Average time of inventory checking 40.93% reducing.